If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4a=6a-3a
We move all terms to the left:
4a-(6a-3a)=0
We add all the numbers together, and all the variables
4a-(+3a)=0
We get rid of parentheses
4a-3a=0
We add all the numbers together, and all the variables
a=0
| 8n+15–3n–5=-40 | | 6a-3a=4a | | 23x+5=34 | | -4x-15=-2x+7 | | 9x-1+12=0 | | 3x-12=5x-24 | | 3u^2+49u+60=0 | | 6x+56=8x+22 | | 425=320+x | | 1/3x=15 | | 1/4x-8=8 | | A12=-7+5(n-1) | | -x+x=72 | | 1/2x=1 | | 1/5x=15 | | 5x-4(x+3)=5 | | 5x–4(x+3)=5 | | 3x^2+2x=18x+4 | | x/4=9.50 | | 2a/5=0 | | 2x+9=3–4x | | x-4=9.50 | | x+4=9.50 | | 4x=9.50 | | 0-0.2x=91 | | -3(3x+2)+10x=5 | | –3(3x+2)+10x=5 | | 2x–1=3x+5+x+1=5. | | X=40+-0.5y | | 9.1-10=0.3x | | 2x+1=3x+5–x–1=5. | | 6•x=120 |